Æ-6 eLena; Conceptual Design of 6-Seater Electric Aircraft - Aini, F N; Prastawa, H; Permana, J I; Dara, K; Ummah, K; Arief, Yanuar Zulardiansyah (International Journal of Aviation Science and Engineering - AVIA, 2024)
Globalization has made a huge impact on worldwide interaction and integration in our lives. Traveling between locations, for instance, has become easier with the advancement of transportation modes such as aircraft. However due to the ever-increasing environmental concerns, alternatives of conventional aviation fuels have become necessary in order to provide more eco-friendly flights. Fortunately, alternatives such as aircraft batteries have become feasible with technology improvements, allowing an idea for resolving the issue, namely the development of an electric aircraft. This paper will be focused on designing a six-seater electric aircraft through parametric studies on several aspects such as aircraft configurations, weight and balance, stability, performance, structures, aerodynamics, and cost analysis while also aiming to meeting the given DRO. The designed aircraft, Æ-6 eLena, has a range of 540 km, a takeoff weight of 3003 kg, a cruising speed of 300 km/hr, and a lift-to-drag ratio of 13.5. The conceptual design of this aircraft is intended to be certified under current CASR 23 regulations, with production beginning in 2026.